Online Sustainability Reporting At Muhammadiyah University In South Selawesi - Chindy Putri Ardhana; Agusdiwana Suarni; Sahrullah (www.amertainstitute.com, 2024)
Purpose: This study aims to examine the current status of online sustainability reporting in the Muhammadiyah University sector in South Sulawesi from various perspectives. Design/methodology/approach: Multiple case study is the research method for this study. Content analysis of university websites and documentation was adopted for data collection. An assessment framework for sustainability reporting was developed as an instrument for content analysis, based on G4 guidelines and previous literature. Findings: According to the research, all Muhammadiyah universities in South Sulawesi still face significant limitations in their sustainability reporting practices. The lack of dedicated pages for sustainability reporting on their official websites and technical issues that render their official websites completely inaccessible demonstrate this. The analysis of nine Muhammadiyah universities in South Sulawesi reveals that the average sustainability reporting standards need substantial improvement, with the economic aspect scoring 5.56, the social aspect scoring 5.89, and the environmental aspect only reaching 3.89. These low scores indicate that Muhammadiyah universities in this region have not yet achieved optimal communication of their activities and achievements to their stakeholders and the surrounding community in their operational environment. This situation requires special attention to enhance both transparency and the quality of sustainability reporting in the future. Social implications: This study highlights that higher education institutions have a fundamental responsibility to implement sustainable practices internally and then communicate these efforts using modern information technology to meet stakeholder responsibilities and the expectations of the surrounding community. Originality/value: This study uses a multiple case study approach to explore online sustainability reporting practices in higher education settings, focusing on the context of Universiti Muhammadiyah in South Sulawesi. This study contributes to the limited research in this area, particularly related to sustainable digital transparency in higher education institutions.